A STUDY ON ENGLISH TEACHERSâ PEDAGOGICAL COMPETENCIES IN TEACHING AND LEARNING PROCESS (A Descriptive Research at SMPN 2 Tembilahan Hulu) - Ahmad, Ahmad; Iratna, Iratna (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2018)
AbstractThe main purpose of this study was to investigate English teachersâ pedagogical cempetencies in teaching and learning process and its supporting factors. It was conducted at the English teachers at SMPN 2 Tembilahan Hulu. It was a descriptive quantitative research. The sample of this study were five English teachers at SMPN 2 Tembilahan Hulu. The data were collected by using questionnaire sheet. By the questionnaire sheet, the researcher got the results that the teachersâ pedagogical competencies in teaching and learning process at SMPN 2 Tembilahan Hulu was at good level with the percentage 73.73%. Where the teachersâ pedagogical competencies of the first teacher was at good level (71.00%), the second teacher was at good level (78.00%), the third teacher was at good level (70.00%). It is the same with the fourth and fifth teacher. They were also at good level (78.00%). By the questionnaire sheet, the researcher also got the results that supporting factors of teachersâ pedagogical competencies in teaching and learning process are dominant on the social environment factor. Based on the result of this study, it revealed taht the English teachers at SMPN 2 Tembilahan Hulu understand and recognize about teachersâ pedagogical competencies in teaching and learning process.Â Keywords: Pedagogical Competencies, Teaching Learning Process.